IN-VITRO EVALUATION OF FUNGICIDES AND BIOAGENTS AGAINST TOMATO EARLY BLIGHT PATHOGEN ALTERNARIA SOLANI (L.) - V. SUMBULA,; S.P KURIAN, (The Bioscan, 2020)
Early blight disease caused by Alternaria solani (L.) is one of the most destructive diseases of tomato in the tropical and subtropical regions. In the present study, efficacy of different fungicides at different concentration and bioagents against A. solani was assessed under in vitro conditions. A total of eight fungicides and seven bioagents were tested. It was found that, all the three concentrations of propineb (0.1%, 0.2% and 0.3%), hexaconazole (0.05%, 0.1% and 0.15%) and iprodione 25% + carbendazim (0.1%, 0.2% and 0.3%) and difenoconazole at 0.075% concentration showed cent per cent inhibition of A.solani. It was followed by lower concentrations of difenoconazole (0.05% and 0.025%) with 97.21 and 94.99 per cent inhibition of pathogen respectively. Among remaining fungicides, all the three concentrations of pyraclostrobin was significantly superior over copper hydroxide, azoxystrobin and trifloxystrobin 25% + tebuconazole in inhibiting mycelial growth and it ranged from 79.44 to 85.55 per cent. Among the bioagents tested, Trichoderma viride (KAU) and plant growth promoting microbial consortium (PGPM mix of KAU) were recorded cent per cent inhibition of pathogen. Among different bacterial antagonists Bacillus subtilis 1; an endophyte isolated from cocoa recorded maximum growth inhibition of 51.66 per cent.